Recent Trends in Nanomaterial Based Electrochemical Sensors for Drug Detection: Considering Green Assessment - Ozer, Tugba; Henry, Charles S. (BENTHAM SCIENCE PUBL LTD, 2024)
An individual's therapeutic drug exposure level is directly linked to corresponding clinical effects. Rapid, sensitive, inexpensive, portable and reliable devices are needed for diagnosis related to drug exposure, treatment, and prognosis of diseases. Electrochemical sensors are useful for drug monitoring due to their high sensitivity and fast response time. Also, they can be combined with portable signal read-out devices for point-of-care applications. In recent years, nanomaterials such as carbon-based, carbon-metal nanocomposites, noble nanomaterials have been widely used to modify electrode surfaces due to their outstanding features including catalytic abilities, conductivity, chemical stability, biocompatibility for development of electrochemical sensors. This review paper presents the most recent advances about nanomaterials-based electrochemical sensors including the use of green assessment approach for detection of drugs including anticancer, antiviral, anti-inflammatory, and antibiotics covering the period from 2019 to 2023. The sensor characteristics such as analyte interactions, fabrication, sensitivity, and selectivity are also discussed. In addition, the current challenges and potential future directions of the field are highlighted.
Keywords: Nanomaterial; Drug; Electrochemical sensors; Green assessment; Pharmaceuticals; Green synthesis; GLASSY-CARBON ELECTRODE; DICLOFENAC SODIUM; MORPHINE; NANOCOMPOSITE; NANOPARTICLES; COMPOSITES; SAFINAMIDE; IRINOTECAN; DOPAMINE; SAFETY; Pharmacology & Pharmacy